CLASSIFICATION OF PRICES AND THEIR CHARACTERISTICS - SACHYNSKA, Liudmyla (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article considers the concept of price from various aspects and its economic essence. It is reflected through the performance of its individual functions, which are interrelated and form a single system: accounting; balancing supply and demand; stimulating; distributive; means of production allocation. The author analyzes various approaches to the classification of prices and their types. Price is understood as a means of marketing influence of an enterprise on a consumer with the aim of ensuring market equilibrium between supply and demand. Price is an important source of income for an enterprise, since it contains profit. Price components also include various types of indirect taxes (value added tax, excise duty), trade or special markups, margins or discounts. The price of goods is finally formed in the market and largely depends on the ratio of supply and demand. In market conditions, if the price is a monetary expression of the exchange value of a commodity, it constantly deviates from the level of the value itself in accordance with changes in demand for products in the process of purchase, sale or commodity exchange. The market price level is formed under the influence of market conditions, but the demand for products offered on the market is of primary importance. Price is a multifaceted economic phenomenon that plays a crucial role in regulating economic processes. Different types of prices have their own characteristics and are applied in appropriate conditions. Understanding price classification helps businesses, governments, and consumers make effective economic decisions. Price classification is an important tool for market analysis. It helps to determine effective pricing strategies for businesses, regulate economic processes, and ensure balanced economic development. New pricing models allow businesses to manage demand more effectively, increase customer loyalty and maximize profits. The price classification is constantly updated in line with changes in the economy, technology and consumer behavior. New approaches to price classification take into account the factors of the digital economy, globalization and individualization of demand.